(untitled) - Despopoulos, Agamemmon (New York, 1991)
Table of contents: General and cellular physiology; Nerve and muscle; Autonomic nervous system; Blood; Respiration; Acid-base balance...
Keywords: Human physiology,Sinh lý học người; Handbooks, manuals, etc.,Sổ tay, sách hướng dẫn, v.v.